2020
DOI: 10.1101/2020.08.13.249771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient non-specific DNA binding dominates the target search of bacterial DNA-binding proteins

Abstract: Despite their diverse biochemical characteristics and functions, all DNA-binding proteins share the ability to accurately locate their target sites among the vast excess of non-target DNA. Towards identifying universal mechanisms of the target search, we used single-molecule tracking of 11 diverse DNA-binding proteins in living Escherichia coli. The mobility of these proteins during the target search was dictated by DNA interactions, rather than by their molecular weights. By generating cells devoid of all chr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 114 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…2). Given that NusG is not known to bind directly to chromosomal DNA, but instead binds to the chromosome indirectly (via RNAP during transcription elongation), we would expect that the D* value and diffusion behaviour of NusG should be independent of the presence of the chromosome, as we have shown for proteins lacking DNAbinding domains (Stracy et al, 2021). However, the D* value for free NusG matches that for a 4times larger protein that is unable to bind DNA (Lac -41 , a ~200 KDa truncated lac repressor (LacI) derivative lacking its DNA-binding domain).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…2). Given that NusG is not known to bind directly to chromosomal DNA, but instead binds to the chromosome indirectly (via RNAP during transcription elongation), we would expect that the D* value and diffusion behaviour of NusG should be independent of the presence of the chromosome, as we have shown for proteins lacking DNAbinding domains (Stracy et al, 2021). However, the D* value for free NusG matches that for a 4times larger protein that is unable to bind DNA (Lac -41 , a ~200 KDa truncated lac repressor (LacI) derivative lacking its DNA-binding domain).…”
Section: Discussionmentioning
confidence: 88%
“…Further, under the same consideration that NusG does not bind directly to chromosomal DNA, the diffusion of free NusG in cells with intact nucleoids should resemble the behaviour of HU-PAmCherry, 48 KDa (same size as NusG-PAmCherry) in cells where the chromosomal DNA has been degraded (DNA-free cells; see (Stracy et al, 2021)). Again, strikingly, while the estimated accurate diffusion coefficient of HU-PAmCherry in DNA-free cells is Dacc ~12.6 μm 2 /s (Stracy et al, 2021), the Dacc for NusG-PAmCherry in cells with intact nucleoids is estimated to be ~3.5 μm 2 /s (based on the similarity of the D* values for NusG-PAmCherry and LacI-PAmCherry, and the conversion of D* to Dacc for LacI-PAmCherry using simulations of diffusion (Stracy et al, 2021)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter description emerges quite naturally when looking at atomic force micrographs of DNA/protein complexes deposited on mica plates ( 5), but simulations have shown that the conformations of DNA/protein complexes are significantly different in bulk and in planar conditions and that the parallel protein bridges geometry arises from the rearrangement of the complexes after their deposition on the charged surface (38,39). Moreover, recent single-molecule experiments have reported the presence of clusters of H-NS proteins buried inside the nucleoid (46), while other experiments have shown that mutants of H-NS, which have disrupted dimer-dimer interactions and cannot form higher order oligomers, are also unable to form bridges between two DNA duplexes (47). The ability for H-NS dimers to clusterize therefore appears as a prerequisite for their ability to bridge distant DNA sites, which strongly supports the conclusions of the present work.…”
Section: The Case Of a Buffer Containing Cations Of Two Different Val...mentioning
confidence: 99%